A more perfect union - Jance, Judith A., 1944- (Avon suspense, 2009)
A shocking photo screamed from the front pages of the tabloids-the last moments of a life captured for all the world to see. The look of sheer terror eternally frozen on the face of the doomed woman indicated that her fatal fall from an upper story of an unfinished Seattle skyscraper was no desperate suicide-and that look will forever haunt Homicide Detective J.P. Beaumont. But his hunt for answers and justice is leading to more death, and to dark and terrible secrets scrupulously guarded by men of steel behind the locked doors of a powerful union that extracts its dues payments in blood.